FEATURES OF THE COURSE AND OUTCOMES OF PREGNANCY IN WOMEN WITH METABOLIC SYNDROME: A REVIEW - Magzumova N.M; Axtamova M.N. (Scholar Express Journals, 2026)
Metabolic syndrome (MetS) is a cluster of metabolic abnormalities including central obesity, insulin resistance, hypertension, and dyslipidemia. The prevalence of metabolic syndrome among women of reproductive age has increased significantly worldwide, leading to a growing number of pregnancies complicated by metabolic disorders. MetS during pregnancy is associated with adverse maternal and perinatal outcomes, including gestational diabetes mellitus, hypertensive disorders, preeclampsia, cesarean delivery, preterm birth, and neonatal metabolic disturbances. This review analyzes literature published between 2015 and 2026 on the course and outcomes of pregnancy in women with metabolic syndrome. Current evidence indicates that metabolic syndrome significantly increases obstetric risks and influences long-term maternal and offspring health. Early diagnosis, multidisciplinary management, and lifestyle interventions improve pregnancy outcomes.
Keywords: Metabolic Syndrome; Pregnancy; Gestational Diabetes